Mutated circulating tumor DNA as a liquid biopsy in lung cancer detection and treatment. Issue 6 (26th May 2021) - Filipska, Martyna; Rosell, Rafael
Abstract : Over the past decade, substantial developments have been made in the detection of circulating tumor DNA (ctDNA)—cell‐free DNA (cfDNA) fragments released into the circulation from tumor cells and displaying the genetic alterations of those cells. As such, ctDNA detected in liquid biopsies serves as a powerful tool for cancer patient stratification, therapy guidance, detection of resistance, and relapse monitoring. In this Review, we describe lung cancer diagnosis and monitoring strategies using ctDNA detection technologies and compile recent evidence regarding lung cancer‐related mutation detection in liquid biopsy. We focus not only on epidermal growth factor receptor ( EGFR ) alterations, but also on significant co‐mutations that shed more light on novel ctDNA‐based liquid biopsy applications. Finally, we discuss future perspectives of early‐cancer detection and clonal hematopoiesis filtering strategies, with possible inclusion of microbiome‐driven liquid biopsy. Abstract : Liquid biopsy can greatly contribute to better detection and management of lung cancer. ctDNA detection in liquid biopsies is a powerful tool for early detection, cancer patient stratification, therapy guidance, detection of resistance, and relapse monitoring. We describe lung cancer diagnosis and monitoring strategies using ctDNA detection technologies and compile recent evidence on the identification of lung cancer‐related mutations through liquid biopsy.